Active initial pre-pressure concrete and construction process thereof
By applying initial steady-state pressure during concrete pouring and using CDG soil as fine aggregate, the problems of high concrete porosity and shortage of fine aggregate are solved, and the mechanical properties and durability of concrete are significantly improved.
Patent Information
- Application Number
- CN202410967096.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-19
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
It is difficult for existing concrete to effectively reduce porosity and permeability during the pouring process, resulting in reduced performance, and excessive mining of traditional fine aggregates such as river sand leads to environmental problems.
During the concrete pouring process, methods and equipment that actively apply initial steady-state pressure are used to pressurize the fresh liquid concrete, significantly reducing the porosity of the concrete, and using CDG soil as an alternative fine aggregate.
Through active initial pre-pressure technology, the density, elastic modulus, compressive strength and tensile strength of concrete can be significantly improved, the porosity and water absorption rate can be reduced, and the early and service life performance of concrete can be improved.
Smart Images

Figure CN119330641A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to high-performance active initial prestressed concrete. More specifically, the present invention relates to applying steady-state prestressing to fresh liquid concrete during the pouring process, thereby significantly reducing the porosity and permeability of concrete components and improving the performance of concrete components, including density, elastic modulus, compressive strength and tensile strength. Background Art
[0002] Concrete is a man-made composite solid material. It is a liquid mixture of aggregate, cement, water and other materials such as additives in appropriate proportions, and then cemented by cement hydration reaction. Due to urbanization and industrialization, concrete has always been the most consumed solid building material in the world in response to the growth of construction demand. The initial state of fresh concrete is liquid, hydration reaction occurs, and it gradually hardens from liquid cementation to a solid material with high elastic modulus and high compressive and tensile strength.
[0003] The mechanical properties and durability of concrete are affected by many factors. For example, the pore structure, pore distribution and porosity inside the concrete are highly correlated with the overall performance. Studies have shown that since concrete is a composite solid material, an increase in its porosity will lead to a decrease in its physical, mechanical and chemical properties. Therefore, eliminating and reducing concrete pores and cracks can effectively improve the performance of concrete. In related fields, literature has proposed different methods to reduce the possibility of pores and cracks in concrete and enhance its mechanical properties such as compressive strength and tensile strength. For example, reinforcing materials such as shrinkage compensation admixtures and fibers are added to concrete.
[0004] Concrete aggregate plays an important role as a skeleton and support, while fine aggregate fills most of the gaps between coarse aggregates, making the mixture evenly distributed and further improving the uniformity of concrete. Fine aggregate also affects the workability, durability and mechanical properties of fresh concrete. The traditional conventional fine aggregate is river sand. However, with the over-exploitation of river sand, this has led to irreversible environmental problems such as land erosion and riverbed changes, that is, facing the problem of river sand shortage. In concrete production operations, the use of alternative fine aggregates is a common solution to the problem of over-exploitation of river sand. Many studies have investigated and tested a variety of different alternative sources of fine aggregates, such as industrial by-products (steel slag, copper slag, etc.), recycled fine aggregates (recycled concrete, recycled plastic, etc.) and stone powder (such as crushed granite fine powder).
[0005] CDG (completely decomposed granite) is completely weathered granite. CDG soil refers to the soil decomposed from granite parent rock (including granite, granodiorite, quartz monzonite, etc.) under the action of physical and chemical weathering. CDG soil is particularly widely distributed in southern China. For example, CDG soil in Hong Kong accounts for about 30% of its total land surface area, and the weathering depth can reach 100 meters below the surface. It is composed of granite. CDG soil is mostly reddish brown with good gradation. Its constituent particles are mainly quartz minerals, clay minerals and a small amount of feldspar and biotite. CDG soil has abundant reserves, wide sources and is easy to obtain. It is usually the main component of the excavated waste soil from construction projects. At present, it is usually used as fill in Hong Kong for land reclamation projects. However, the main mineral component of CDG soil is quartz, which is similar to traditional fine aggregate river sand and alternative aggregate granite powder. In view of this, the current industry needs a method to properly utilize CDG, which can use CDG as a raw material to develop new alternative aggregates for concrete. Summary of the invention
[0006] The object of the present invention is to provide a method and apparatus for actively applying an initial steady-state pressure during concrete pouring to prepare high-performance concrete components and maintain an active confinement effect in the concrete material.
[0007] According to one aspect of the present invention, a method for actively applying an initial steady-state pressure to fresh liquid (or semi-liquid) concrete is provided, characterized in that it comprises: adding materials such as aggregate, cement and water into a container to form a liquid mixture; stirring the mixture to obtain a fresh liquid concrete mixture; pouring the fresh liquid mixture into a mold or a template, and smoothing the surface of the fresh mixture after the mold is filled; installing a top plate with one or more hollow cylinders on the mold or the template to cover the fresh liquid mixture, thereby sealing the mold or the template; the inner diameter of the hollow cylinder is tens to hundreds of millimeters. m (or, for example, an inner diameter of 10 mm to 1000 mm); pouring additional fresh liquid mixture into the hollow cylinder and smoothing the top mixture surface; gently placing a cylinder piston on the surface of the fresh liquid mixture in the hollow cylinder; pressurizing the piston to apply a steady-state pressure to the fresh liquid mixture in the completely sealed mold or formwork, so that the fresh liquid mixture in the hollow cylinder becomes a part of the fresh mixture in the mold or formwork; after applying the steady-state pressure for several hours, unloading the piston pressure; when the mixture has hardened to a sufficient strength, removing the mold or formwork to obtain a concrete component.
[0008] In some embodiments, the initial pressure is in the range of 1 MPa to 50 MPa.
[0009] In some embodiments, the mold or formwork is determined according to the size of the concrete component.
[0010] In some embodiments, after applying the initial pressure and before the step of unloading the pressure, the method further comprises: maintaining the applied pressure at a steady state for a given time.
[0011] The present invention provides a pressurizing system for carrying out the aforementioned method, comprising: a cylindrical, cubic or other sized mold or formwork portion; a loading portion, arranged above the mold or formwork portion; a hollow cylinder, a cylindrical piston and a hydraulic jack or hydraulic cylinder and other devices, driving the loading portion; a hydraulic jack or hydraulic cylinder, connected to the cylindrical piston, so as to cooperate to pressurize the cube or other mold or formwork portion, so as to apply an active initial steady-state pressure to the freshly mixed liquid concrete mixture in the mold or formwork.
[0012] According to the present invention, a method for applying active initial pressure to fresh liquid mortar and concrete and pouring the same is provided, which is characterized in that it comprises: mixing materials such as water, cement and aggregate in a container to form a mixture; stirring the mixture with a stirrer to form a fresh liquid mixture; placing a bottom piston in a hollow cylindrical mold; placing the fresh liquid mixture in the cylindrical mold; placing a top piston in the hollow cylindrical mold; positioning the hollow cylindrical mold on a bottom load sensor; applying pressure to the top piston with a hydraulic jack to apply pressure to the fresh liquid mixture for compression; unloading the top piston pressure after applying steady-state pressure for several hours; and demolding the hardened mortar or concrete in the mold by moving the bottom piston upward.
[0013] In some embodiments, after applying pressure to the fresh liquid mixture, the pressure is maintained at a steady state for a specified period of time, and after the specified period of time, the pressure is unloaded.
[0014] In some embodiments, during the process of applying the pressure to the fresh liquid mixture, the method also includes: moving the top piston downward (or moving the bottom piston upward), wherein the bottom (or top) piston remains stationary and causes the fresh liquid mixture in the hollow cylindrical mold to be compressed.
[0015] In this regard, some traditional methods include adding fiber reinforced materials to the concrete pouring process to make concrete (fiber reinforced concrete; FRC) and prestressed concrete. However, FRC reduces the fluidity and construction performance of concrete materials, and prestressed concrete structures require complex construction processes and prestressed tendons. Pressurization technology can effectively improve the quality of mortar.
[0016] In the technical solution of the present invention, the potential of using CDG soil as an aggregate substitute is studied. CDG soil is an easily accessible and environmentally friendly raw material that comes from a by-product of excavation operations and has low cost. Therefore, considering using CDG soil, which is abundant in reserves and easy to obtain, to replace river sand as concrete aggregate is a green and environmentally friendly technical solution. CDG soil is currently mainly used as filler in reclamation projects. Compared with the direct economic benefits of being a filler, CDG soil has greater potential as an aggregate substitute in concrete production. In addition, the active initial pre-compression application technology and method provided by the present invention can be used to apply an initial steady-state pressure to a freshly mixed liquid concrete mixture, which can effectively improve the quality of concrete construction. Therefore, the construction industry and concrete manufacturing, prefabricated structures and modular structures (Modular Integrated Construction; MiC) technology may benefit.
[0017] The present invention relates to a new type of concrete material, in particular to an improved high-performance concrete material for high-performance structural engineering applications. The rapid construction of high-performance infrastructure requires the use of durable high-early-strength materials to quickly reach high strength within a few hours after pouring. The present invention includes a new type of active pre-confined concrete (APC) material, which has high early strength, high final strength, high modulus and low porosity. Active pre-confined concrete can introduce pressure into the concrete during the pouring process, thereby significantly reducing the porosity of the concrete, increasing the compressive strength of the concrete material to 150MPa and the tensile strength to 20MPa. High-early-strength APC materials can reduce the curing time of concrete materials, thereby significantly reducing the construction time of engineering structures. Compared with ordinary concrete, the final strength is increased by at least 10MPa. When APC is poured together with steel bars or wire mesh, after demolding, the pre-tension stress in the steel bars and the pre-compression stress in the concrete material will be automatically formed. Therefore, by pouring active pre-stressed concrete into the steel tube, the mechanical properties of the active pre-confined concrete filled tube (APCFT) can be significantly enhanced, and the steel tube will transfer axial and circumferential tensile strength as a permanent formwork, while the internal APC will bear true triaxial compressive prestress, thereby significantly improving the ultimate strength and stiffness of the component under complex loads. In this way, the cracks in the concrete will be reduced, the local buckling of the steel tube will be reduced, and the ultimate bearing capacity of the specimen will be improved.
[0018] During the pouring process, a steady-state pressure is applied to the fresh liquid concrete mixture by an active initial pre-stressing device, and the initial active pressure will maintain a steady state for a short period of time (for example, from 6 hours to 24 hours) before the concrete material solidifies. After that, the pressure can be unloaded. The steel formwork of the concrete can be removed or retained as a permanent formwork to form a steel-concrete composite structure. Due to the initial pre-stressing applied to the fresh liquid concrete material, the porosity of the concrete component is significantly reduced, thereby improving the tensile strength and compressive strength of the concrete component at an early stage and during its service life.
[0019] Therefore, the combination of initial active prestressed concrete and other building materials (such as steel bars, steel fibers, steel tubes or fiber-reinforced polymers) can introduce initial multi-directional compressive prestress into the concrete, which will significantly improve the performance of the final structural components. Therefore, initial active prestressed concrete materials can be applied to the requirements of complex engineering structures, including but not limited to high-rise buildings, long-span bridges, immersed tube tunnels and special engineering projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] These and / or other aspects and advantages of the present invention will become apparent and more easily understood by referring to the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 Depicts standard sands (such as Xiamen standard sand and CDG soil) used as fine aggregates for making mortar and concrete, where: Figure 1 Part (a) is the image of CDG soil and Xiamen standard sand; Figure 1 Part (b) is the weight percentage of different parts of CDG soil and Xiamen sand; Figure 1 Part (c) is the gradation curve of different particle types of CDG soil and Xiamen sand.
[0022] Figure 2 Some embodiments of the present invention are depicted as follows: (a) is an image of a device; and (b) is a schematic cross-sectional view of the device.
[0023] Figure 3 According to some embodiments of the present invention, the following are depicted: (a) is a schematic diagram of the design of a device; and (b) is a schematic diagram of the design of a device.
[0024] Figure 4 The mechanical relationship and motion diagram of each part of the device during the pressurization process are shown.
[0025] Figure 5The pouring procedure of ordinary mortar and concrete specimens without initial active pre-stressing is depicted, wherein: part (a) is stirring the mixture using an electric stirrer; part (b) is adding lubricating oil to the inner surface of the mold; part (c) is compacting the mixture using a compacting rod; part (d) is removing the excess mixture and leveling the surface; part (e) is demoulding the mortar or concrete specimen; and part (f) is the specimen after curing for 28 days.
[0026] Figure 6 Depicted is the casting procedure for mortar and concrete specimens subjected to initial active prestressing, where: (a) part is mounting the mold with screws; (b) part is adding lubricant to the inner surface of the mold; (c) part is adding the fresh liquid mixture to the mold; (d) part is mounting the top plate with screws; (e) part is adding additional mixture to the hollow cylinder; (f) part is mounting the pressure sensor; (g) part is mounting the linear variable differential transformer (LVDT); and (h) part is the specimen with initial pressure after curing for 28 days.
[0027] Figure 7 Part (a), part (b), part (c), and part (d) are pictures of hardened CDG mortar and mortar specimens without initial active preloading (mixing ratio of water: cement: aggregate = 0.5:1:1); Figure 7 Part (e), part (f), part (g), and part (h) are pictures of CDG concrete and concrete with (without) initial active preloading.
[0028] Figure 8 and Fig. 9 The time variations of the applied axial force and the displacement induced by the piston for the CDG mortar specimen and the CDG concrete specimen are shown, respectively.
[0029] Fig.10 and Fig.11 The variations of the axial force applied and the induced piston displacement with time for the mortar specimen and concrete specimen are shown respectively.
[0030] Fig.12 The relationship between volumetric strain and stress for all six pressurized mortar and four pressurized concrete specimens according to some embodiments of the present invention is shown, where Fig.12 : Part (a) is the volume strain-stress curve of CDG mortar specimen; Part (b) is the volume strain-stress curve of CDG concrete specimen; Part (c) is the volume strain-stress curve of mortar specimen; Part (d) is the volume strain-stress curve of concrete specimen.
[0031] Fig.13Depicted are: (a) a graph showing the density variation of 12 mortar specimens made with CDG or sand at different mixing ratios under an initial pressure of 5 MPa or 0 MPa; (b) a graph showing the density variation of CDG mortar and sand mortar with the same mix ratio (0.5:1:1) under different initial pressure values.
[0032] Fig.14 Depicted are: (a) the variation of axial compressive strength values of 12 mortar specimens made of CDG soil or sand with different mixing ratios under initial pressure of 5 MPa or 0 MPa; (b) the variation of axial compressive strength values of CDG mortar and mortar with the same ratio (0.5:1:1) under different initial pressure values.
[0033] Fig.15 Depicted are: (a) the variation of water absorption values of 12 mortar specimens made of CDG soil or sand with different mixing ratios under initial pressure of 5 MPa or 0 MPa; (b) the variation of water absorption values of CDG mortar and sand mortar using the same ratio (0.5:1:1) under different initial pressure values.
[0034] Fig.16 Depicted are: (a) part of the CT image of the mortar specimen using zero-pressurized CDG; (b) part of the CT image of the mortar specimen using 5MPa-pressurized CDG; (c) part of the CT image of the mortar specimen using zero-pressurized sand; (d) part of the CT image of the mortar specimen using 5MPa-pressurized sand; (e) part of the Image J analysis of the mortar using zero-pressurized CDG; (f) part of the Image J analysis of the mortar using 5MPa-pressurized CDG; (g) part of the Image J analysis of the mortar using zero-pressurized sand; (h) part of the Image J analysis of the mortar using 5MPa-pressurized sand.
[0035] Fig.17 The variation of density values of eight concrete specimens manufactured with CDG or sand as fine aggregate in different mix ratios under an initial pressure of 5 MPa or 0 MPa is depicted.
[0036] Fig.18 The variation of axial compressive strength of eight concrete specimens manufactured with CDG or sand as fine aggregate in different mix ratios under initial compression of 5 MPa or 0 MPa is depicted.
[0037] Fig.19 The variation of water absorption values of 8 concrete specimens made with CDG or sand as fine aggregate at different mix ratios under initial pressure of 5 MPa or 0 MPa is depicted.
[0038] Fig. 20Depicted are: (a) a CT image of a concrete specimen using CDG under zero pressure; (b) a CT image of a concrete specimen using CDG under 5 MPa pressure; (c) a CT image of a concrete specimen under zero pressure; (d) a CT image of a concrete specimen under 5 MPa pressure; (e) an Image J analysis of CDG concrete under zero pressure; (f) an Image J analysis of CDG concrete under 5 MPa pressure; (g) an Image J analysis of concrete under zero pressure; (h) an Image J analysis of concrete under 5 MPa pressure.
[0039] Fig.21 Depicted are CDG and sand, fine aggregates used to make mortar, where: (a) is an image of CDG; (b) is an image of Xiamen sand; (c) is a gradation curve of CDG soil and Xiamen sand and a graph of the weight percentage of different particle types.
[0040] Fig. 22 An experimental setup 20 was made for the initial pressurized mortar specimens.
[0041] Fig.23 This is the pouring step of the mortar specimen with initial pressurization of 0 / 10MPa.
[0042] Fig.24 The pressure and piston displacement of the CDG mortar specimen are shown as a function of time.
[0043] Fig.25 The pressure and piston displacement of the mortar specimen are shown as a function of time.
[0044] Fig.26 Depicted are: (a) the stress-volume strain curve of the CDG mortar specimen; (b) the stress-volume strain curve of the mortar specimen.
[0045] Fig. 27 Pictures of six mortar and CDG mortar samples with three typical mix ratios are depicted.
[0046] Fig.28 Pictures of six mortars with three typical mix ratios and six CDG mortars are shown.
[0047] Fig.29 The graph shows the density variation relationship of multiple mortar specimens made of CDG and Xiamen standard sand under initial pressure of 10MPa or 0MPa and different water contents.
[0048] Fig.30 The graph shows the change relationship of uniaxial compressive strength of multiple mortar specimens made of CDG and Xiamen standard sand under initial pressure of 10MPa or 0MPa and different water contents.
[0049] Fig.31 CT images and data analysis of representative specimens are depicted, where: Part (a), Part (b), Part (c), and Part (d) are cross-sectional CT images of pressurized and zero-pressurized CDG and concrete specimens; Part (e) is the cumulative density gradation curve. DETAILED DESCRIPTION
[0050] In the following description, a pressurized manufacturing device and / or method for high-quality mortar and concrete using sand and CDG as fine aggregates and water / cement / CDG mixtures will be described as preferred examples. Modifications, including additions and / or substitutions, may be made to those skilled in the art without departing from the scope and spirit of the invention. Specific details may be omitted to avoid obscuring the invention; however, this disclosure is written to enable those skilled in the art to implement the teachings of the invention without undue experimentation.
[0051] In the present invention, two corresponding technical solutions are provided. Please note that these technical solutions are not intended to limit the technical means provided by the present invention. They are only to more comprehensively illustrate the potential of the pre-pressurization process provided by the present invention, and to propose that such technical means are flexible and can flexibly modify parameters to meet actual needs.
[0052] Technical solution (I) is a preparation process for initial pressurization of mortar and concrete using water / cement / CDG mixture, CDG soil and sand as fine aggregate; Technical solution (I) will be described below.
[0053] In technical solution (I), the effectiveness of applying high compressive pressure to the initial liquid mixture of mortar and concrete was first studied. In some embodiments, completely decomposed granite (CDG) soil is used as an alternative fine aggregate in the production of mortar and concrete; and the designed experimental device is used to apply pressure. In this regard, by applying initial pressure, excess voids and air in the fresh liquid mortar and concrete can be removed, thereby enhancing the mechanical properties. In some embodiments, two types of fine aggregates, two mixing ratios and two initial pressure values are used to manufacture a total of 8 cubic concrete specimens. In some embodiments, two types of fine aggregates, three mixing ratios and two initial pressure values are used to manufacture a total of 12 cubic mortar specimens. On the other hand, 10 cubic mortar specimens are made using CDG and sand as fine aggregates and hardened at five initial pressure values.
[0054] In the present invention, tests including density, uniaxial compressive strength (axial compressive strength), and water absorption are performed to compare the quality of the samples; and micro-CT images are used to quantify the porosity of the specimens. The results show that initial pressurization can significantly increase the density and uniaxial compressive strength of mortar and concrete specimens with CDG and sand as fine aggregates, and reduce the porosity and water absorption. At the same time, the density and axial compressive strength of CDG mortar both increase with the increase of initial pressure values. The test results provide verification for the use of initial compaction pressure on fresh liquid mixtures to manufacture high-performance mortar and concrete. The present disclosure thus provides a potential technical means for using CDG soil as fine aggregate in the mortar and concrete production industry.
[0055] [Technical Solution (I) - Part 1: Materials and Methods]: The materials and methods of Technical Solution (I) are described here, including the materials applied or adopted, experimental equipment and specimen preparation.
[0056] [Technical Solution (I) - Part 1.1: Materials]: Figure 1 Depicts standard sands (such as Xiamen standard sand and CDG soil) used as fine aggregates for making mortar and concrete, where: Figure 1 Part (a) is the image of CDG soil and Xiamen standard sand; Figure 1 Part (b) is the weight percentage of different parts of CDG soil and Xiamen sand; Figure 1 Part (c) is the gradation curve of different particle types of CDG soil and Xiamen sand. The strength grade of the Portland cement used in the test is 52.5N. According to some standards, Figure 1 Xiamen ISO standard sand (or Xiamen sand or sand) shown in part (a) of the present invention is used as fine aggregate to cast ordinary mortar and concrete to compare the results of mortar and concrete with CDG soil as fine aggregate. In some embodiments, the fine aggregate CDG soil used is as follows: Figure 1 As shown in part (b) of .
[0057] [Technical Solution (I) - Part 1.2: Experimental Setup]: Figure 2 According to some embodiments of the present invention, the following are depicted: (a) is a portion of an image of a device; (b) is a portion of a schematic cross-sectional view of a device; Figure 3 According to some embodiments of the present invention, the following are depicted: (a) is a schematic diagram of the design of the device; (b) is a schematic diagram of the design of the device. In order to maintain the same conditions as the conventional concrete cube test, the provided device is designed to apply pressure to the fresh liquid concrete during the hardening duration. The device can apply an initial pressure of 5 to 30 MPa to the fresh liquid mortar and concrete in a completely sealed cube mold. Pictures and parts details of the pressurization system are shown in Figure 1. Figure 2 and Figure 3 The pressurizing system 10 can be divided into a cube mold part 100 and a loading part 102 .
[0058] The loading part 102 is arranged above the cubic mold part 100. The pressurizing system 10 includes a hydraulic cylinder 104, a sensor 106, a Belleville spring 108, a piston 110, a screw member 112, a mold 114, a hydraulic jack 116, and a leak-proof rubber pad 118. The mold 114 can serve as the main body of the cubic mold part 100 and can be fixed by the screw member 112. The piston 110 is connected to the mold 114 of the cubic mold part 100. The lower end of the Belleville spring 108 is connected to the piston 110, and the upper end of the Belleville spring 108 is connected to the sensor 106. The hydraulic cylinder 104 is connected to the sensor 106, and the loading part 102 can be driven by the hydraulic cylinder 104, wherein the hydraulic jack 116 is connected to the hydraulic cylinder 104, so that the mold 114 of the cubic mold part 100 can be loaded or pressurized in cooperation. In addition, in the cubic mold part 100, a leak-proof rubber pad 118 is used to prevent the slurry of the target test piece from overflowing, and a combination of an upper seal and a lower seal can also be used to further achieve leak-proofing.
[0059] [Technical Solution (I) - Section 1.2.1: Cube Mold Part]: Regarding the cube mold part, such as Figure 2 and Figure 3 The cubic mold 114 has an outer dimension of 380×380×310 cubic millimeters and an inner dimension of 150×150×150 cubic millimeters. It is a detachable structure, consisting of 6 33 mm thick plates, and its periphery and inner seals are pre-pressed structures, fastened with high-strength screws of screw members 112, and each joint is provided with a leak-proof rubber pad 118. There is a pit with a height of 200 mm at the center of the top plate, and a vertical hollow steel pipe with an inner diameter of 60 mm is fixed to replenish the newly mixed liquid mortar or concrete.
[0060] [Technical Solution (I) - Section 1.2.2: Loading Section]: The loading section is 1000 mm high and includes a hydraulic cylinder 104, a hydraulic jack 116, a piston 110, four steel columns, three steel bearing plates, four groups of six Belleville springs 108, a vertical load sensor and a vertical displacement sensor of the sensor 106. The piston 110 can be tightly and smoothly inserted into the hollow cylinder to transmit the pressure to the fresh liquid mortar or concrete in the cubic mold 114. The piston 110 adopts a double-layer sealing method and its effective loading length is 140 mm. The vertical load can be applied by the hydraulic cylinder 104 and the hydraulic jack 116. The Belleville spring 108 can act as a buffer to prevent the bearing plate and the piston 110 from loosening over time.
[0061] [Technical Solution (I) - Section 1.2.3: Force transmission during pressurization]: Regarding force transmission during pressurization, the pressurization device is a self-balancing device. Figure 4 The mechanical relationship and motion diagram of each part of the device during the pressurization process are shown.
[0062] For the hydraulic cylinder, G is the weight of the hydraulic cylinder. F1' is the reaction force of each screw. Therefore, G=4F′...(1)
[0063] For piston, F Hydraulic The pressure provided to the hydraulic jack, F Concrete1 is the reaction force of the concrete mixture in the cavity. Therefore, F Hydraulic =F Concrete1 …(2)
[0064] For the upper support plate of the cube mold, F Concrete2 is the reaction force of the concrete mixture in the cubic mold, and F′1 is the tension of each screw. F Concrete2 =2F′=2F′1...(3)
[0065] For liquid concrete mixture, P is the pressure exerted on the concrete mixture and N is the reaction force provided by the lower plate of the mold. P×Area concrete =F Hydraulic +2F Concete2 =F Concrete1 +2FConcrete2…(4) N×Areaconcrete=P×Areaconcrete ete =F Concrete1 +2FConcrete2…(5)
[0066] [Technical Solution (I) - Section 1.3: Specimen Preparation]: Specimen preparation may include zero initial pressurization specimens and 5 MPa initial pressurization specimens (or, the initial pressure used for initial pressurization may be in the range of 1 MPa to 50 MPa).
[0067] [Technical Solution (I) - Section 1.3.1: Zero Initial Pressurized Specimen]: Figure 5 The pouring procedure of mortar and concrete specimens with zero initial pressure is depicted, where: part (a) is stirring the mixture using an electric stirrer; part (b) is adding lubricating oil to the inner surface of the mold; part (c) is compacting the mixture using a compacting rod; part (d) is removing the excess mixture and leveling the surface; part (e) is demoulding the mortar or concrete specimen; and part (f) is the specimen after curing for 28 days.
[0068] For mortar and concrete with zero initial pressure, the pouring procedure can follow the requirements of existing building standards. Use a cubic mold of 150*150*150 cubic millimeters. Figure 5 As shown, the pouring process can be summarized as the following steps: 1) Put aggregate, cement and water into a container (such as a steel drum) in sequence and mix them evenly with an electric stirrer. The aggregate of the mortar specimen is only fine aggregate, namely Xiamen sand or CDG soil; the aggregate of the concrete specimen is 20 mm coarse aggregate and 10 mm coarse aggregate. 2) Add lubricating oil to the inner surface of the cubic mold to facilitate subsequent demoulding. 3) Put the freshly mixed liquid mortar or concrete into the mold in three layers. Each layer is about 50 mm thick and compacted 50 times with a compacting rod. Use a steel trowel to remove excess mortar or concrete above the edge of the mold; then, smooth the surface of the mixture. 4) After 24 hours, demould the mortar or concrete specimen and test its size and weight. 5) Put the specimen in water at 27±3℃ and cure for 28 days.
[0069] [Technical Solution (I) - Section 1.3.2: Test piece with 5 MPa initial pressurization]: Figure 6 The casting procedure of mortar and concrete specimens with initial pressure is depicted, where: (a) part is installing the mold with screws; (b) part is adding lubricating oil to the inner surface of the mold; (c) part is adding the fresh liquid mixture to the mold; (d) part is installing the top plate with screws; (e) part is adding additional mixture to the hollow cylinder; (f) part is installing the pressure sensor; (g) part is installing the linear variable differential transformer (LVDT); (h) part is the specimen with initial pressure after curing for 28 days.
[0070] Specifically, for mortar and concrete with initial pressure, the pouring process is as follows Figure 6As shown. The pouring process is as follows: 1) Install the cubic mold and the leak-proof rubber pads at each joint, and tighten the screws outside the mold. 2) After the mold is installed, add lubricating oil to the inner surface of the mold. 3) Pour the liquid or semi-liquid freshly mixed liquid mortar or concrete into the mold in three layers. The thickness of each layer is also about 50 mm, and it is compacted 50 times with a compacting rod. 4) Install the top plate, install the top plate with screws, and tighten the screws on the top plate, wherein the top plate has a hollow cylinder at its center. In some embodiments, the purpose of using the top plate at this stage is to completely seal the mold 5) Add additional freshly mixed liquid mortar and concrete to the hollow cylinder in the center of the top plate, and the freshly mixed liquid mixture in the hollow cylinder is also compacted 50 times. 6) Install the peripheral screws of four columns and three load-bearing plates. 7) Install the piston, disc spring, sensor, data logger, hydraulic cylinder, and hydraulic jack in sequence. 8) Use a pressurizing device to apply an initial pressure to the freshly mixed liquid mortar or concrete mixture and additional freshly mixed liquid mortar and concrete in a completely sealed mold. For this purpose, a hydraulic system can be used to pressurize to the required pressure. In some embodiments, the initial pressure used is in the range of 1MPa to 50MPa; or in the range of 5MPa to 30MPa; or in the range of 5MPa to 10MPa; or only a pressure value of 5MPa or 10MPa is selected. 9) Release the pressure and remove the pressurizing device, and then demold the mortar or concrete specimen from the cubic mold. 10) After measuring the size and weight of the specimen, place it in 27±3℃ water and cure it for 28 days.
[0071] Figure 7 Part (a), part (b), part (c), and part (d) are pictures of representative hardened CDG mortar and mortar specimens with and without initial pressure application (mixing ratio of water:cement:aggregate = 0.5:1:1). Figure 7 Part (e), part (f), part (g), and part (h) are representative CDG concrete and concrete pictures with and without initial pressure (mixing ratio is water:cement:fine aggregate:coarse aggregate = 0.5:1:1:2.5).
[0072] [Technical Solution (I) - Section 1.3.3: Changes in pressure and displacement during pressurization]: During the initial pressurization process, when the hydraulic jack and the hydraulic cylinder apply an axial force to the piston, the piston moves downward and transmits the axial force to the fresh liquid mixture in the hollow cylinder and the cube mold. The changes in the axial force applied to the liquid mixture and the displacement caused by the piston over time are measured and recorded by force sensors and LVDTs, respectively. Since the fresh liquid mixture in the cube mold and the hollow cylinder is in a liquid or semi-liquid state, its operation can apply Pascal's principle, so that the piston can transmit its pressure to all the fresh liquid mortar or concrete. At the same time, the piston can push the fresh liquid mortar and concrete in the hollow cylinder into the cube mold to compensate for the fresh liquid mixture in the cube mold. Figure 8 and Fig. 9 The time variations of the applied axial force and the displacement induced by the piston for the CDG mortar specimen and the CDG concrete specimen are shown, respectively. Fig.10 and Fig.11 The variations of the axial force applied and the induced piston displacement with time for the mortar specimen and concrete specimen are shown respectively.
[0073] according to Figures 8 to 11 , when the hydraulic system is used to apply initial pressurization to the fresh liquid mortar, the applied axial force first increases to 17-20KN at a linear speed within 20-60s. The axial force causes the subsequent vertical displacement of the piston to change with time; then the axial force is stopped. Since the piston is still moving downward and the hydraulic system cannot maintain a constant axial force level, the value of the force begins to decrease rapidly, resulting in a gradual slowing down of the descent speed. Finally, the axial force value stabilizes at 13-15KN around 40-80 seconds.
[0074] In the figure, the displacement of the piston represents the compression displacement of the mixture in the hollow cylinder, which means that the corresponding height of the cylindrical mortar mixture is added to the cube. Figure 8 , Fig. 9 As shown in the figure, after the axial force is applied to both CDG mortar specimens and mortar specimens, the piston displacement increases linearly except for fluctuations, and the increase rate gradually slows down; 120 to 140 seconds after the force is applied, the displacement value finally stabilizes at 80 to 90 mm. It can be seen that with the linear increase of the applied axial force, the piston displacement also increases linearly. When the force value stabilizes, the displacement value continues to increase in 40 to 100 seconds until it reaches a stable point.
[0075] For fresh liquid concrete specimens, specifically, Fig.10 and Fig.11 The changes in the axial force and displacement caused by the fresh liquid CDG concrete and concrete in the first 150 seconds of initial pressurization are shown respectively. Fig.10 and Fig.11 As shown in Figure 2, for fresh liquid concrete specimens, the variation trend of the axial force is similar to that of the mortar specimens. The value of the applied axial force first reaches a peak value of 18-22KN at a roughly linear rate within 20-50 seconds. Once the axial force is stopped, its value begins to decrease. Finally, the force value stabilizes at 14-16KN around 80-100 seconds.
[0076] For the CDG concrete and concrete specimens, after the pressure was applied to the initial liquid mixture, the displacement also increased linearly at first and then stabilized at 25–35 mm at 50–70 s. Figure 8 , Fig. 9 , Fig.10 , Fig.11 It can be seen that the displacement value of the concrete specimen stabilizes earlier than that of the mortar specimen. When the axial force applied to the fresh liquid concrete reaches its maximum value, the displacement of the piston continues to increase for 20-40 seconds. When the piston displacement stabilizes, the applied force is also stable. In addition, the displacement value of the concrete specimen is much lower than that of the mortar specimen.
[0077] Regarding the change in volumetric strain with applied axial stress during the initial pressurization process, since the height of the vertical hollow cylinder is 200 mm and the inner diameter of the cylinder is 60 mm (or the inner diameter of the hollow cylinder can be 10 mm to 1000 mm), when pressure is applied, the stress and volumetric strain of the fresh liquid mixture can be calculated using the following formula.
[0078] Fig.12 The relationship between volumetric strain and stress for all six pressurized mortar and four pressurized concrete specimens according to some embodiments of the present invention is shown, where Fig.12 :Part (a) is the volume strain-stress curve of CDG mortar specimen; Part (b) is the volume strain-stress curve of CDG concrete specimen; Part (c) is the volume strain-stress curve of mortar specimen; Part (d) is the volume strain-stress curve of concrete specimen. Fig.12 Part (a) and Fig.12 As shown in part (c), the stress variation over time of the CDG mortar and mortar specimens follows the same pattern as the applied pressure: it increases initially, then decreases after reaching a peak value, and finally stabilizes at the corresponding value. Despite the stable stress value, the volume of the fresh liquid mortar mixture in the mold continues to change. In contrast, the fresh liquid concrete exhibits lower compressibility than the fresh liquid mortar due to the presence of coarse aggregate in the concrete mixture. According to Fig.12 Part (a) and Fig.12In part (c), the stress variation trends of CDG mortar and mortar specimens are the same as the variation trends of applied pressure over time; Fig.12 Part (b) and Fig.12 In part (d), for CDG concrete and concrete specimens, the volumetric strain values of the mixtures tend to be stable, while the stress values continue to decrease. Finally, the stress values of the initial fresh mortar and concrete tend to be stable and remain between 4.5 and 6 MPa. The volumetric strain of the mortar specimens is stable between 0.055–0.065, while the volumetric strain of the concrete specimens is stable between 0.018–0.024.
[0079] [Technical Solution (I) - Part 2: Results and Discussion of Cube Mortar]: The results and discussion of the cube mortar provided by Technical Solution (I) will be stated here, including density, uniaxial compressive strength (axial compressive strength), water absorption, and X-ray fractional observation. According to some standards, the cube mortar mixture can be designed according to three weight ratios of water: cement: aggregate: 0.5:1:2, 0.5:1:1.5, and 0.5:1:1. Two fine aggregates, CDG and sand, were used for comparative test studies at two initial pressure values (0 / 5MPa) for 24 hours. Therefore, a total of 12 cube mortar specimens were made. Four performance tests of density, axial compressive strength, water absorption, and porosity were carried out on the hardened specimens.
[0080] [Technical Solution (I) - Part 2.1: Density Results]: Fig.13 Depicted are: (a) a graph showing the density variation of 12 mortar specimens made with CDG or sand at different mixing ratios under an initial pressure of 5 MPa or 0 MPa; (b) a graph showing the density variation of CDG mortar and sand mortar with the same mix ratio (0.5:1:1) under different initial pressure values.
[0081] Regarding the density results, the dimensions and weight of the hardened mortar specimens were measured after demoulding and before curing. The density of the mortar specimens can then be calculated. The density values of the 12 mortar specimens prepared with CDG or sand as aggregate at 5 MPa or without initial pressure at different mix ratios are shown in the figure below: Fig.13 The results are shown in part (a) of , and Table 1. Table 1: Density test results of 12 CDG or mortar specimens with or without initial pressure of 5 MPa
[0082] [Technical Solution (I) - Section 2.1.1: Effect of Mixing Ratio]: Regarding the effect of mixing ratio, for both pressurized and non-pressurized specimens, the density values of mortar specimens with a mixing ratio of 0.5:1:1.5 are higher than those of specimens with other ratios. As the aggregate ratio increases from 0.4 (water: cement: aggregate = 0.5:1:1) to 0.57 (water: cement: aggregate = 0.5:1:2), the density value increases first and then decreases. For example, the density values of the three CDG mortars with an initial pressure of 5 MPa are 2021, 2119, and 2090 kg / m3, respectively, when the mixing ratios are 0.5:1:1, 0.5:1:1.5, and 0.5:1:2.
[0083] [Technical Solution (I) - Section 2.1.2: Effect of Different Aggregates]: Regarding the effect of different aggregates, in general, the density values of mortar specimens prepared with CDG were lower than those of mortar specimens using sand as aggregate under both pressurized and non-pressurized conditions. When a pressure of 5 MPa was applied for 24 hours, the density of CDG mortar with a density of 0.5:1:2 (2090 kg / m3) could be slightly higher than the density of mortar without initial pressurization (1991 kg / m3) under the same conditions. These results indicate that initial pressurization can make the density values of CDG mortar specimens similar or higher than those of conventional mortars using sand as aggregate.
[0084] [Technical Solution (I) - Section 2.1.3: Effect of Initial Pressurization]: Regarding the effect of initial pressurization, such as Fig.13 As shown in part (a), the initial pressure of 5MPa can significantly increase the density values of all CDG or sand specimens with three mix ratios. The average density of CDG specimens with three mix ratios pressurized by 5MPa can reach 2077 kg / m3, and the average density of three CDG specimens with initial pressure of 0MPa can reach 2000 kg / m3, and the average density value of CDG mortar increases by 3.85%. The average density of three mortar specimens with initial pressure of 5MPa is 2148 kg / m3, and the average density of mortar without initial pressure is 2067 kg / m3, and the average density value of mortar increases by 3.92%. It can be seen that the initial pressure of 5MPa can significantly increase the density values of all specimens with different mix ratios and fine aggregates. For CDG mortar and mortar, the effect of pressure on density improvement is similar.
[0085] Fig.13Part (b) of and Table 2 show the changes in density values of CDG mortar and mortar with the same mix ratio (0.5:1:1) at different initial pressure values. It can be seen that with the increase of the initial pressurization value, the density values of CDG mortar and mortar both increase. It can be seen from the figure that before the pressure value reaches 20MPa, the growth rate of CDG mortar with the increase of pressure value is higher than that of mortar. However, with the increase of initial pressure value, the density growth rate of CDG mortar and mortar gradually slows down. For example, the density of 5MPa pressurized CDG mortar is 2021 kg / m3, which is 3.38% higher than 1955 kg / m3 of unpressurized CDG mortar. The density of 10MPa pressurized CDG mortar is 2054 kg / m3, which is 5.06% higher than that of unpressurized CDG mortar. When the initial pressure increases from 10MPa to 15MPa and 20MPa, the growth rate of the specimen density value slows down. The density of 15MPa pressurized CDG mortar and 20MPa pressurized CDG mortar are 6.29% and 7.01% higher than that of the unpressurized specimen, respectively. Table 2: Density test results of 8 CDG or mortar specimens (mix ratio = 0.5:1:1) at different initial pressure values
[0086] [Technical Solution (I) - Part 2.2: Axial Compressive Strength Results]: Fig.14 Depicted are: (a) the variation of axial compressive strength values of 12 mortar specimens made of CDG or sand with different mixing ratios under initial pressure of 5 MPa or 0 MPa; (b) the variation of axial compressive strength values of CDG mortar and sand mortar with the same ratio (0.5:1:1) under different initial pressure values.
[0087] After the hardened mortar specimens were cured for 28 days, the uniaxial compressive strength (axial compressive strength) test was carried out. The changes in the axial compressive strength values of 12 mortar specimens with different mixing ratios using CDG soil and sand as fine aggregate under an initial pressure of 5MPa or 0MPa are shown in Figure 2. Fig.14 As shown in part (a) and Table 3. Table 3: Axial compressive strength test results of 12 CDG or mortar specimens with initial pressure of 5 MPa or without initial pressure
[0088] [Technical Solution (I) - Section 2.2.1: Effect of Mixing Ratio]: Regarding the effect of mixing ratio, in general, the axial compressive strength values of pressurized and non-pressurized mortar specimens with a mixing ratio of 0.5:1:1.5 are higher than those of specimens with other ratios. As the aggregate ratio increases from 0.4 (water: cement: aggregate = 0.5:1:1) to 0.57 (water: cement: aggregate = 0.5:1:2), the axial compressive strength value first increases and then decreases. For example, the axial compressive strength values of the three CDG mortars with an initial pressure of 5 MPa are 42.276, 48.269, and 32.973 MPa, respectively, when the mixing ratios are 0.5:1:1, 0.5:1:1.5, and 0.5:1:2.
[0089] [Technical Solution (I) - Section 2.2.2: Influence of Different Aggregates]: Due to the influence of different aggregates, the axial compressive strength values of non-pressurized CDG mortar specimens are much lower than those of non-pressurized mortar specimens. However, under 5MPa pressure, the axial compressive strengths of CDG mortar specimens with a mixing ratio of 0.5:1:1 and 0.5:1:1.5 are 42.276MPa and 48.269MPa, respectively, which are higher than the 37.656MPa and 47.072MPa of the 5MPa pressurized mortar specimens. These results show that the axial compressive strength values of non-pressurized mortar specimens with CDG soil as fine aggregate are affected by the presence of clay minerals in CDG soil. After initial pressurization, the axial compressive strength values of CDG mortar specimens can be higher than or close to the axial compressive strength values of non-pressurized and pressurized mortar specimens.
[0090] [Technical Solution (I) - Section 2.2.3: Effect of Initial Pressurization Value]: Regarding the effect of initial pressurization value, similar to the change in density value, 5MPa initial pressurization can significantly increase the axial compressive strength values of CDG mortar and mortar with three mix ratios. The average axial compressive strength value of 5MPa pressurized CDG mortar specimens with three mix ratios is 41.173MPa. The average axial compressive strength value of unpressurized CDG mortar is 29.896MPa. The average axial compressive strength value of CDG mortar after pressurization increased by 37.72%. The average axial compressive strength of the three mortar specimens with an initial pressurization of 5MPa was 43.658MPa, while the average axial compressive strength of the three unpressurized mortar specimens was 40.474MPa. The average axial compressive strength of the mortar specimens increased by 7.87%. Therefore, the technical means of initial pressurization can improve the axial compressive strength of all specimens with different mix ratios and fine aggregates. Moreover, the initial pressurization has a greater effect on improving the axial compressive strength of CDG mortar specimens, which is far greater than that of mortar specimens.
[0091] Fig.14Part (b) and Table 4 show the changes in the axial compressive strength values of CDG mortar and mortar with the same mix ratio (0.5:1:1) at different initial pressure values. It can be seen that as the initial pressure value increases from 5MPa to 10MPa, the axial compressive strength values of CDG mortar and mortar increase significantly. For example, for CDG mortar, when a pressure of 5MPa is applied, an axial compressive strength value of 42.276MPa can be obtained, which is 82.29% higher than the 23.191MPa of unpressurized CDG mortar; when a pressure of 10MPa is applied, an axial compressive strength value of 52.168MPa can be obtained, which is 23.40% higher than the 5MPa pressurized CDG mortar. When the pressure increases to 15MPa and 20MPa, the growth rate of the axial compressive strength of the mortar gradually slows down, while the axial compressive strength of the CDG mortar stops growing. The axial compressive strengths of the CDG mortars under 15MPa and 20MPa pressures are 51.379MPa and 51.563MPa, respectively, which are similar to the axial compressive strength of the CDG mortar under 10MPa pressure. Table 4: Axial compressive strength test results of 8 CDG or mortar specimens (mix ratio = 0.5:1:1) with different initial pressure values
[0092] [Technical Solution (I) - Part 2.3: Influence of Water Absorption Results]: Fig.15 Depicted are: (a) the changes in water absorption values of 12 mortar specimens made of CDG or sand with different mix ratios under initial pressure of 5 MPa or 0 MPa; (b) the changes in water absorption values of mortar and sand using the same ratio (0.5:1:1) of CDG at different initial pressure values. After demoulding, the mortar specimens were immersed in 20°C water for curing for 28 days. The weight of the mortar specimens before and after curing was measured respectively. The water absorption is defined as the amount of water absorbed, which is calculated as the ratio of the weight increased during curing to the initial dry weight of the specimen before curing. The higher the water absorption value, the easier it is for corrosive substances to penetrate into the pore system of concrete, and the worse the durability of the concrete. For the 12 mortar specimens made with CDG and sand as fine aggregate, the changes in their water absorption values at different mix ratios and different initial pressure values are shown in Figure 2. Fig.15 As shown in part (a) and Table 5. Table 5: Water absorption test results of 12 CDG or mortar specimens with initial pressure of 5MPa or without initial pressure
[0093] [Technical Solution (I) - Section 2.3.1: Effect of Mixing Ratio Results]: As for the effect of mixing ratio, for the unpressurized CDG and mortar specimens, the water absorption values decreased as the mixing ratio changed from 0.5:1:1 to 0.5:1:2. The mortar specimens with a mixing ratio of 0.5:1:2 without initial pressurization had the lowest water absorption.
[0094] [Technical Solution (I) - Section 2.3.2: Effect of Different Aggregates]: In terms of the effect of different aggregates, the unpressurized CDG mortar has a water absorption value similar to that of the unpressurized mortar. However, when a pressure of 5 MPa is applied, the water absorption of the CDG mortar is lower than that of the mortar specimens. The average water absorption of the unpressurized CDG mortar is 18.045%, which is 1.67% lower than the water absorption of the unpressurized mortar of 18.351%. The average water absorption of the CDG mortar pressurized with 5 MPa is 12.527%, which is 13.6% lower than the water absorption of the mortar of 14.499%, indicating that the initial pressurization can make the water absorption of the CDG mortar specimens much lower than that of the mortar specimens.
[0095] [Technical Solution (I) - Section 2.3.3: Effect of Initial Pressurization Value]: Regarding the effect of initial pressurization value, as shown in the figure, the initial pressurization of 5MPa can significantly reduce the water absorption of CDG mortar and mortar with three different mixing ratios. Combined with the method of calculating the average water absorption value proposed in Section 2.3.2, it can be seen that the average water absorption values of CDG mortar and mortar after pressurization are reduced by 30.58% and 20.99%, respectively. This shows that initial pressurization can also reduce the water absorption values of all specimens with different mix ratios and fine aggregates, thereby improving the durability of the specimens. And the reduction in water absorption of CDG mortar specimens is more obvious than that of mortar specimens.
[0096] Fig.15 Part (b) of Figure 6 and Table 6 show the changes in water absorption values of CDG mortar and mortar with a mix ratio of 0.5:1:1 under different initial pressure values. As the initial pressure increases from 5MPa to 10MPa, the water absorption values of CDG mortar and mortar both decrease significantly. For example, for CDG mortar, the water absorption decreases from 19.396% to 12.423% with an initial pressure of 5MPa, a decrease of 35.85%; when a pressure of 10MPa is applied, the water absorption decreases to 5.906%, which is 52.46% lower than that of CDG mortar pressurized at 5MPa. As the initial pressure further increases to 15MPa and 20MPa, the rate of decrease in water absorption of CDG mortar slows down, and the water absorption of CDG mortar pressurized at 15MPa is 26.77% lower than that of CDG mortar pressurized at 10MPa; when the pressure increases from 15MPa to 20MPa, the decrease rate is only 3.24%. Table 6: Water absorption test results of 8 CDG or mortar specimens (mix ratio = 0.5:1:1) at different initial pressure values
[0097] [Technical Solution (I) - Part 2.4: X-ray Fractional Observation]: In the following content, image analysis and comparison of porosity, volume, and density changes will be performed by using Image J.
[0098] [Technical Solution (I) - Section 2.4.1: Image analysis using Image J]: Fig.16 Depicted are: (a) part of the CT image of the mortar specimen using zero-pressurized CDG; (b) part of the CT image of the mortar specimen using 5MPa-pressurized CDG; (c) part of the CT image of the mortar specimen using zero-pressurized sand; (d) part of the CT image of the mortar specimen using 5MPa-pressurized sand; (e) part of the Image J analysis of the mortar using zero-pressurized CDG; (f) part of the Image J analysis of the mortar using 5MPa-pressurized CDG; (g) part of the Image J analysis of the mortar using zero-pressurized sand; (h) part of the Image J analysis of the mortar using 5MPa-pressurized sand.
[0099] The microstructure of CDG and mortar specimens with a water:cement:aggregate ratio of 0.5:1:2 was tested using a scanner (Micro CT ScannerTOSCANER-3000) while image analysis was performed using Image J. Fig.16 The four CT images in parts (a), (b), (c), and (d) represent two CDG mortar specimens and two mortar specimens under initial pressure of 5 MPa and 0 MPa, respectively. The areas of all pores in the CT images were calculated using the software Image J. Fig.16 Parts (e) to (h) of 16 show the selection and labeling of pores in the software. The porosity can be calculated by dividing the total pore area by the total area of the slice. The porosity of the CDG mortar specimen with zero pressure is 10.476%, and the porosity of the CDG mortar specimen with 5 MPa pressure is 1.893%. The porosity of the mortar specimen with zero pressure is 6.247%, and the porosity of the mortar specimen with 5 MPa pressure is 1.124%.
[0100] The calculation results show that the porosity of CDG and mortar specimens with an initial pressure of 5MPa is 81.93% and 82.01% lower than that of unpressurized CDG and mortar specimens, respectively, which means that the initial pressure of 5MPa can significantly reduce the porosity. The porosity of the unpressurized CDG mortar specimen is 10.476%, which is significantly higher than the 6.247% of the unpressurized mortar specimen, but when the initial pressure is 5MPa, the porosity of the CDG mortar specimen drops to 1.893%, which is basically the same as the 1.124% porosity of the mortar specimen. The results show that initial pressure can significantly reduce the porosity of CDG and mortar specimens and produce CDG mortar with a porosity similar to that of the mortar specimen.
[0101] [Technical Solution (I) - Section 2.4.2: Comparison of porosity, volume and density changes]: Regarding the comparison of porosity, volume and density changes, for the 5MPa pressurized CDG mortar specimens and mortar specimens, the fresh liquid mortar mixture (including Figure 2 and Figure 3 The relationship between porosity and total volume of the cubes and hollow cylinders shown is as follows.
[0102] Assume that ρ1 is the density of the mixture before pressurization, ρ2 is the density of the mixture after pressurization; n1 is the porosity of the mixture before pressurization, n2 is the porosity of the mixture after pressurization; m is the total weight of the mixture in the mold; V1 is the total volume of the mixture in the mold before pressurization; V2 is the total volume of the mixture in the mold after pressurization. Therefore, we can get:
[0103] According to the definition, we can get: ρ1=(1-n1)G s (1+ω)ρ ω …(10) ρ2=(1-n2)G s (1+ω)ρ ω …(11)
[0104] Substituting equations (9) and (10) into equation (8), we obtain:
[0105] Therefore, the relationship between the total porosity and volume of the mortar mixture before and after initial pressurization should conform to formula (11).
[0106] According to section 2.2.1, in some embodiments, the optional configuration includes: the cavity inner diameter is 0.06 m, the cavity height is 0.2 m, and the cube inner dimensions are 0.15 m×0.15 m×0.15 m. According to the above formula (7), the volume (V1) of the specimen before pressurization is 0.00394 m3.
[0107] For the CDG mortar specimen with a mixing ratio of water: cement: fine aggregate = 0.5: 1: 2, when a pressure of 5 MPa is applied, the final stable displacement of the piston is 86.87 mm. Calculated from the CT image, the porosity of the zero-pressure CDG mortar is 10.476%, which can be regarded as n1. The porosity of the 5 MPa-pressure CDG mortar is 1.893%. Therefore, it can be obtained:
[0108] For the CDG mortar specimens with this ratio, we can obtain:
[0109] The density of the unpressurized CDG mortar with a mix ratio of 0.5:1:2 is 2033 kg / m3, which can be regarded as ρ1; while the density of the 5MPa pressurized CDG mortar is 2090 kg / m3, which is ρ2.
[0110] For the mortar specimen with a mixing ratio of 0.5:1:2, when a pressure of 5MPa is applied, the final stable displacement of the piston is 81.95 mm. Calculated from the CT image, the porosity of the zero-pressurized mortar is 6.247%, which can be regarded as n1. The porosity of the 5MPa pressurized mortar is 1.124%, which can be regarded as n2. Therefore:
[0111] Therefore, for the mortar specimen with this ratio, we can obtain:
[0112] On the other hand, in the absence of initial pressurization, the density of the mortar with a mix ratio of 0.5:1:2 is 1991 kg / m3, which can be regarded as ρ1, while the density of the mortar pressurized with 5 MPa is 2058 kg / m3, which can be regarded as ρ2. in:
[0113] These results indicate that there is a close correlation between the changes in porosity, volume, and density of CDG and mortar before and after initial pressurization.
[0114] [Technical Solution (I) - Part 3: Results and Discussion of Cube Concrete]: The results and discussion of the cube concrete of Technical Solution (I) will be presented here, including density, axial compressive strength, water absorption, and X-ray fraction observation.
[0115] According to some criteria, cubic concrete mixes can be designed with the following two weight ratios: water: cement: fine aggregate: coarse aggregate, 0.5:1:1:2.5 and 0.5:1:1.5:2.5 respectively. Two fine aggregate types CDG and sand and two initial pressure values (0 / 5MPa) were applied for 24 hours for comparative experimental study. For this, a total of 8 cubic concrete specimens were manufactured. The density, axial compressive strength, water absorption and porosity of the concrete specimens were also tested.
[0116] [Technical Solution (I) - Section 3.1: Density]: Regarding density, Fig.17 The variation of density values of 8 concrete specimens made with CDG or sand as fine aggregate in different mix ratios under initial pressure of 5 MPa or 0 MPa is depicted. The dimensions and weight of the hardened concrete specimens can be measured after demoulding and before curing. Then, the density of these specimens can be calculated. Fig.17 and Table 7 show the changing relationship of the density values of 8 concrete specimens manufactured with CDG or sand as fine aggregate in different mixing ratios under an initial pressure of 5 MPa or 0 MPa. Table 7: Density test results of 8 CDG or concrete specimens with initial pressure of 5MPa or without pressure
[0117] [Technical Solution (I) - Section 3.1.1: Effect of Mixing Ratio]: Regarding the effect of mixing ratio, for both pressurized and non-pressurized concrete specimens, the specimens with a mixing ratio of 0.5:1:1.5:2.5 (water: cement: fine aggregate: coarse aggregate) showed higher density values. The average density value of the concrete specimens with this mixing ratio was 2306 kg / m3, which was 1.59% higher than the average density value of 2270 kg / m3 of the concrete specimens with a mixing ratio of 0.5:1:1:2.5.
[0118] [Technical Solution (I) - Section 3.1.2: Effect of Different Fine Aggregates]: Regarding the effect of different fine aggregates, the density values of pressurized and non-pressurized concrete specimens using CDG as fine aggregate are lower than those of specimens using sand as fine aggregate. The average density of the concrete without pressurization is 2320 kg / m3, which is 4.46% higher than the 2221 kg / m3 of the unpressurized CDG concrete. When the initial pressure is 5MPa, the average density of the concrete is 2351 kg / m3, which is only 3.98% higher than the 2261 kg / m3 of the CDG concrete. These results show that the improvement effect of initial pressurization on CDG concrete specimens is more significant than that on concrete specimens.
[0119] [Technical Solution (I) - Section 3.1.3: Effect of Initial Pressurization Value]: Regarding the effect of initial pressurization value, according to the determination in Section 3.1.2, under the initial pressurization of 5MPa, the average density value of CDG concrete increased from 2221 kg / m3 to 2261 kg / m3, an increase of 1.8%. Similarly, under the same conditions, the average density value increased from 2320 kg / m3 to 2351 kg / m3, an increase of 1.34%. This shows that initial pressurization can significantly increase the density values of all specimens with different mix ratios and fine aggregates.
[0120] [Technical Solution (I) - Part 3.2: Axial Compressive Strength]: Regarding axial compressive strength, Fig.18 And Table 8 depicts the changes in axial compressive strength values of eight concrete specimens manufactured with CDG or sand as fine aggregate in different mix ratios under initial compression of 5 MPa or 0 MPa. Table 8: Axial compressive strength test results of 8 CDG or concrete specimens with initial pressure of 5MPa or without pressure
[0121] [Technical Solution (I) - Section 3.2.1: Effect of Mixing Ratio]: Regarding the effect of mixing ratio, similar to the change in density value, both pressurized and non-pressurized CDG and concrete specimens with a mixing ratio of 0.5:1:1.5:2.5 (water: cement: fine aggregate: coarse aggregate) showed higher axial compressive strength values. The average axial compressive strength value of the four concrete specimens using this mixing ratio was 50.1 MPa, which was 4.5% higher than the average axial compressive strength value of 47.9 MPa of the concrete specimens using the mixing ratio of 0.5:1:1:2.5.
[0122] [Technical Solution (I) - Section 3.2.2: Effect of Different Fine Aggregates]: Regarding the effect of different fine aggregates, the axial compressive strength value of the non-pressurized CDG concrete specimens is slightly lower than that of the non-pressurized concrete specimens. However, when an initial pressure of 5MPa is applied, the axial compressive strength values of the CDG concrete specimens with a mix ratio of 0.5:1:1:2.5 and 0.5:1:1.5:2.5 are 53.0MPa and 54.1MPa, respectively, while the axial compressive strength values of the pressurized 5MPa concrete specimens are 51.6MPa and 54.2MPa, respectively. The average axial compressive strength value of the non-pressurized CDG concrete specimens is 44.7MPa, which is 0.54% lower than the average axial compressive strength value of the concrete specimens of 45.0MPa. Under an initial pressure of 5 MPa, the average axial compressive strength of CDG concrete specimens can increase to 53.5 MPa, which is 1.29% higher than the average axial compressive strength of concrete specimens, which is 52.9 MPa. Such results show that initial pressure can increase the axial compressive strength of CDG concrete specimens to a level equivalent to or higher than that of unpressurized and pressurized concrete specimens.
[0123] [Technical Solution (I) - Section 3.2.3: Effect of Initial Pressurization Value]: Regarding the effect of initial pressurization value, an initial pressurization of 5MPa can significantly improve the axial compressive strength values of CDG concrete and concrete specimens with two different mix ratios. The average axial compressive strength value of the two 5MPa pressurized CDG concrete specimens is 53.5MPa, which is 19.67% higher than the average axial compressive strength value of 44.7MPa of the unpressurized CDG concrete specimens. For concrete specimens, an initial pressurization of 5MPa can increase the average axial compressive strength value by 17.5%, from 45.0MPa to 52.9MPa. Therefore, initial pressurization can improve the axial compressive strength values of all specimens, regardless of the fine aggregate type or mix ratio. In addition, the effect of initial pressurization on improving the axial compressive strength value of CDG concrete specimens will be greater.
[0124] [Technical Solution (I) - Section 3.3: Water Absorption]: Regarding water absorption, Fig.19 The variation of water absorption values of 8 concrete specimens made with CDG or sand as fine aggregate at different mix ratios under initial pressure of 5 MPa or 0 MPa is depicted. Table 9: Water absorption test results of 8 CDG concrete or concrete specimens under 5MPa initial pressure or no pressure
[0125] [Technical Solution (I) - Section 3.3.1: Effect of Mix Ratio]: In terms of the effect of mix ratio, CDG and concrete specimens with a mix ratio of 0.5:1:1.5:2.5 (water: cement: fine aggregate: coarse aggregate) have lower water absorption. The average water absorption of the specimens using this mix ratio is 6.599%, which is 6.37% lower than the average water absorption of the specimens with a mix ratio of 0.5:1:1:2.5, which is 7.048%.
[0126] [Technical Solution (I) - Section 3.3.2: Effect of Different Fine Aggregates]: In terms of the effect of different fine aggregates, the average water absorption of the unpressurized CDG concrete specimens is 7.71%, which is close to the average water absorption of the unpressurized concrete specimens, which is 7.939%. However, with an initial pressure of 5MPa, the water absorption of the CDG concrete specimens can be lower than that of the concrete specimens. The average water absorption of the two 5MPa pressurized CDG concretes is 5.062%, which is 23.1% lower than the water absorption of the 5MPa pressurized concrete specimens, which is 6.583%. Therefore, it can be proved that the use of initial pressure can make the water absorption of the CDG concrete specimens much lower than that of the concrete specimens.
[0127] [Technical Solution (I) - Section 3.3.3: Effect of Initial Pressurization Value]: Regarding the effect of initial pressurization value, 5MPa initial pressurization can significantly reduce the water absorption of concrete specimens with all different fine aggregates and mix ratios. As previously determined, the average water absorption of 5MPa pressurized CDG concrete is 5.062%, which is 34.34% lower than the 7.71% of unpressurized CDG concrete. In contrast, the average water absorption of concrete under 5MPa initial pressurization is reduced by 17.08%. These results show that the use of initial pressurization has a greater effect on reducing the water absorption of CDG concrete specimens.
[0128] [Technical Solution (I) - Section 3.4: X-ray Fractional Observation]: In the following content, image analysis using Image J and comparison of porosity, volume, and density changes are included.
[0129] [Technical Solution (I) - Section 3.4.1: Image analysis using Image J]: Fig. 20Depicted are: (a) a CT image of a concrete specimen using CDG under zero pressure; (b) a CT image of a concrete specimen using CDG under 5 MPa pressure; (c) a CT image of a concrete specimen under zero pressure; (d) a CT image of a concrete specimen under 5 MPa pressure; (e) an Image J analysis of CDG concrete under zero pressure; (f) an Image J analysis of CDG concrete under 5 MPa pressure; (g) an Image J analysis of concrete under zero pressure; (h) an Image J analysis of concrete under 5 MPa pressure.
[0130] Regarding the image analysis using Image J, similar to the porosity analysis of the mortar specimens, the microstructure of the slices of CDG and concrete specimens with a water:cement:fine aggregate:coarse aggregate ratio of 0.5:1:1:2.5 was observed using a scanner (Micro CT scanner). Fig. 20 The four CT images in parts (a), (b), (c), and (d) represent two CDG concrete specimens and two concrete specimens under initial pressure of 5 MPa and 0 MPa, respectively. The areas of all pores in the CT images were also calculated using the software Image J. Fig. 20 Parts (e), (f), (g), and (h) show the selection and marking of pores in the software, thereby calculating the porosity.
[0131] The porosity of the unpressurized CDG concrete specimen is 2.45%, and the porosity of the 5MPa pressurized CDG concrete specimen is 0.102%. The porosity of the unpressurized concrete specimen is 2.222%, and the porosity of the 5MPa pressurized concrete specimen is 0.28%.
[0132] The porosity of CDG and concrete specimens with an initial pressure of 5 MPa was 95.84% and 87.4% lower than that of unpressurized CDG and concrete specimens, respectively. This indicates that the porosity of CDG and concrete specimens can be significantly reduced by the initial pressure. The porosity of unpressurized CDG concrete was 2.45%, which was 10.26% higher than the porosity of concrete, 2.22%. However, when subjected to an initial pressure of 5 MPa, the porosity of CDG concrete was reduced to 0.102%, which was 63.57% lower than the porosity of concrete, 0.28%. The results show that the use of initial pressure has a greater effect on reducing the porosity of CDG concrete, and CDG concrete with a lower porosity than concrete can be produced.
[0133] [Technical Solution (I) - Section 3.4.2: Comparison of Porosity, Volume and Density Changes]: A comparison of porosity, volume and density changes is provided here. For CDG and concrete specimens pressurized at 5MPa, the relationship between the porosity and the total volume of the freshly mixed liquid concrete mixture in the mold is consistent with that of the CDG and concrete specimens, as described in the aforementioned formula (9-12). For CDG concrete specimens with a mixing ratio of water: cement: fine aggregate: coarse aggregate = 0.5: 1: 1: 2.5, when a pressure of 5MPa is applied, the final stable displacement of the piston is 31.03 mm. Calculated from CT images, it can be concluded that the porosity of zero-pressurized CDG concrete is 2.45%, while the porosity of 5MPa-pressurized CDG concrete is 0.102%, so it can be obtained:
[0134] Therefore, for the CDG concrete specimen with this ratio, we have:
[0135] The density of unpressurized CDG concrete with a mix ratio of 0.5:1:1:2.5 is 2185 kg / m3, which can be regarded as ρ1; while the density of 5MPa pressurized CDG concrete is 2254 kg / m3, which can be regarded as ρ2.
[0136] For the concrete specimen with the same mix ratio, when pressurized to 5MPa, the final stable displacement of the piston is 26.37mm. Calculated from the CT image, the porosity of the zero-pressurized concrete is 2.222%, which can be regarded as n1. The porosity of the 5MPa-pressurized concrete is 0.28%, which can be regarded as n2. Therefore, it can be obtained:
[0137] Therefore, for the concrete specimens of this proportion, we can obtain:
[0138] On the other hand, without initial pressure, the density of concrete with a mix ratio of 0.5:1:1:2.5 is 2312 kg / m3, which can be considered as ρ1, while the density of concrete after 5MPa pressure is 2350 kg / m3, which can be considered as ρ2. Therefore, we can get:
[0139] These results indicate that there is a close correlation between the changes in CDG and the porosity of concrete specimens, the total volume of fresh liquid concrete, and the density of hardened concrete specimens before and after initial pressurization.
[0140] [Technical Solution (I) - Part 4: General Discussion]: As described above, in the technical solution (I) of the present disclosure, the pressurizing device provided by the present invention can apply a variable pressure to the initial liquid mixture of fresh liquid mortar and concrete to remove excess air and voids therein. In the present disclosure, the effectiveness of initial pressurization in enhancing the performance and mechanical properties of hardened mortar and concrete using different fine aggregates and mixing ratios is demonstrated.
[0141] The above results show that the use of initial pressure can significantly improve the properties of CDG and mortar and concrete by increasing the density and axial compressive strength values while reducing water absorption and porosity. In addition, applying higher initial pressure values to the fresh liquid mortar will obtain hardened mortar with higher density and axial compressive strength and lower water absorption. These performance demonstrations can indicate that the use of initial pressure has the potential for practical engineering applications in the production of high-quality mortar and concrete.
[0142] On the other hand, CDG soil contains 49.83% clay component particles, which have a large specific surface area and high water absorption. This affects the hydration reaction of cement and the bonding between aggregate and cement. Therefore, compared with unpressurized mortar and concrete, unpressurized CDG mortar and concrete exhibit lower density and axial compressive strength values and higher water absorption and porosity. However, initial pressurization has a greater effect on improving the properties of mortar and concrete using CDG as fine aggregate, increasing the density and axial compressive strength values to levels comparable to or even higher than those of pressurized mortar and concrete. This shows that CDG soil also has the potential to be used as fine aggregate to produce high-quality mortar and concrete with initial pressurization.
[0143] Tables 10 and 11 show a summary of these properties. Specifically, under the condition of applying an initial pressure of 5 MPa, the density values of mortar and concrete can increase by about 1% to 8%, the axial compressive strength values can increase by about 10% to 80%, the water absorption can be reduced by 15% to 40%, and the porosity can be significantly reduced by 80% to 95%. It is worth noting that increasing the initial pressure level can make the concrete material have excellent mechanical properties. The axial compressive strength value of the pressurized specimen can increase by up to 122.34%, and the water absorption rate can be reduced by up to 77.77%. It can be seen that the use of initial pressure can help to enhance the potential of manufacturing enhanced high-performance concrete materials in the context of high-quality structural engineering applications. Table 10: Summary of properties of mortar specimens with initial pressure of 5 MPa Table 11: Summary of properties of concrete specimens with initial pressure of 5 MPa
[0144] The mixing ratios shown in the table are only for reference. In practice, they can be adjusted appropriately between these ratios. For example, the water / cement / aggregate ratios are 0.5:1:1, 0.5:1:1.5, and 0.5:1:2 in the table, which means that such a ratio can also be expressed as 0.5:1:X, and X is a number between 1 and 2. In some embodiments, X can also be other ratios within this range, for example, the water / cement / aggregate ratio can be .5:1:1.2 or .5:1:1.7.
[0145] On the other hand, the use of CDG soil as fine aggregate affects the hydration reaction of cement and the bonding between aggregate and cement. Non-pressurized CDG mortar and concrete show lower density and axial compressive strength values and higher water absorption and porosity. However, initial pressurization has a greater effect on improving the performance of CDG concrete materials, increasing the density and axial compressive strength values to levels comparable to those of pressurized mortar and concrete, or even to higher levels. This also shows that CDG soil has the potential to act as a fine aggregate in the production of high-quality mortar and concrete with initial pressurization.
[0146] The following content is the technical solution (two) of the present invention, which corresponds to the technical solution (one), but some configurations or details are modified to make the technical means of initial pressurization more flexible.
[0147] Technical solution (II): Initial pressurization of water-cement-CDG mixture for high-quality mortar
[0148] In technical solution (ii), the effectiveness of applying high compressive pressure to the initial solidification of liquid mixtures is provided. As mentioned above, completely decomposed granite (CDG) soil is used as an alternative fine aggregate for producing high-quality mortar. In this regard, another test device of the present invention is used to carry out a pressure test. In addition, a total of multiple mortar specimens are made using 2 kinds of fine aggregates, 6 mix ratios of 3 kinds of raw materials, 2 initial pressure values, and 2 initial pressure times. For these specimens, their density and uniaxial compressive strength (axial compressive strength) are tested to compare their quality, and their porosity is quantified using Micro CT images. The results show that initial pressure can remove excess moisture and air in the freshly mixed liquid mortar, increase the density and axial compressive strength of CDG soil mortar specimens and mortar specimens, and reduce porosity. The test results provide a reference for applying higher compressive pressure during the initial setting of liquid mixtures and using CDG soil as fine aggregate to make mortar.
[0149] [Technical Solution (II) - Part 1: Materials and Methods]: The following describes the materials and methods used in Technical Solution (II), including the materials applied or adopted, the experimental apparatus and procedures, the changes in pressure and displacement during the pressurization process, and the preparation of the specimens.
[0150] [Technical Solution (II) - Part 1.1: Materials]: Fig.21 CDG and sand of fine aggregate used to make mortar are depicted, wherein: (a) is a CDG image; (b) is a Xiamen sand image; (c) is a gradation curve of CDG soil and Xiamen sand and a weight percentage diagram of different particle types. In some embodiments, the strength grade of the Portland cement used in the test is 52.5N.
[0151] like Fig.21 CDG soil can be excavated from a construction site, and after wet sieving and dry sieving, the overall gradation curve of CDG soil can be as shown in part (a) of FIG. Fig.21 It will be in accordance with some standards and will also use Xiamen ISO standard sand (or Xiamen sand or sand, its characteristics are as follows Fig.21 Ordinary mortar was cast as shown in part (c) of the study to compare the results of mortar with CDG as aggregate.
[0152] [Technical Solution (II) - Part 1.2: Experimental Apparatus and Procedures]: Fig. 22 An experimental device 20 is prepared for the initial pressurized mortar specimen; Fig.23 The details of the mortar preparation experimental device are as follows: Fig.23 As shown, the experimental device used can be composed of a hydraulic jack, a steel hollow cylinder (50 mm in diameter and 150 mm in height), two pistons (50 mm in diameter and 20 mm in height) and a steel reaction template.
[0153] like Fig.23 As shown in the figure, the pouring process can be summarized into the following 12 steps: 1) Weigh water, cement, and fine aggregate. 2) Mix the ingredients in a bucket and stir with an electric stirrer. 3) Place the bottom piston in the cylinder and add lubricating oil to facilitate subsequent demoulding. 4) Place the liquid mixture in the cylindrical mold and vibrate it on a vibration table for 1 minute. Smooth the surface of the liquid mixture in the cylinder. 5) For zero-pressurized specimens, place the mold containing the mortar mixture for 24 hours. These steps are as follows: Fig.23 As shown in parts (a), (b), (c) and (d) of .
[0154] Next, for the specimen with an initial pressurization of 10MPa, the top piston is placed in the hollow cylindrical mold and the cylinder is placed on the bottom load sensor of the equipment. Then, a compressive pressure (10MPa) is applied to the liquid mixture using a hydraulic jack system. 6) During the pressurization process, the bottom load sensor moves upward and the bottom piston is pushed accordingly. The top piston is fixed by the top load sensor, and then the liquid mixture in the jacket is compressed. The force sensor connected to the top load sensor and the LVDT (Linear Variable Differential Transformer) records the pressure value applied to the mixture and the height of the compressed mixture. 7) Keep the pressure constant for a given time (8 or 24 hours). 8) After a given time (8 or 24 hours), unload the pressure. Then the bottom load sensor and the bottom piston move downward. 9) De-mould the hardened mortar. Remove the upper piston and hold and stabilize the jacket with your hands. Apply pressure using a hydraulic pump. As the lower load sensor moves upward, the hardened specimen is pushed out of the jacket. For the specimen without pressurization, the hardened mortar is demolded using the same method. These steps are as follows Fig.23 As shown in parts (e), (f) and (g) of .
[0155] Then, 10) measure the size and weight of the mortar specimen. 11) cure the specimen in 20℃ water for 14 days. 12) then test the hardened specimen. These steps are as follows: Fig.23 As shown in part (h) of .
[0156] [Technical Solution (II) - Part 1.3: Changes in pressure and displacement during pressurization]: Fig.24 The pressure and piston displacement of the CDG mortar specimen are shown as a function of time. Fig.25 The pressure and piston displacement of the mortar specimens change with time. In this stage, the pressure and piston displacement changes with time within the first 300 seconds of pressurization were recorded by force sensors and LVDT (Linear Variable Differential Transformer), respectively. The curves of CDG mortar and mortar with three mixing ratios (0.4:1:1.25, 0.5:1:1.25, 0.7:1:1.25) are shown in Figure 2. Fig.24 and Fig.25 shown.
[0157] like Fig.24 Part (a) and Fig.25 As shown in part (a) of Figure 1, when the hydraulic cylinder is initially pressurized, the applied axial force first rises to 20-22 kN at a roughly linear rate within 40-50 seconds, which causes the piston to vertically displace over time. Then the axial force is stopped. At this stop moment, the hydraulic system cannot maintain a constant axial force level due to the increasing piston displacement, and the applied axial force begins to drop rapidly. The rate of axial force drop gradually slows down, and finally stabilizes at 9-11 kN around 80-140 seconds.
[0158] For example Fig.24 Part (b) and Fig.25 As shown in part (b) of the diagram, once the axial force is applied, the piston begins to move downward under the action of the applied force, and the freshly mixed liquid mortar in the cylinder is compressed. The piston first moves downward at a nearly linear rate, and the displacement slows down 40-50 seconds after the axial force is applied. Finally, around 130-180 seconds, the piston displacement stabilizes at 14-19 mm. Fig.24 and Fig.25 It can be seen that as the applied axial force increases linearly, the piston displacement also increases linearly. When the force stops increasing, the piston displacement continues to increase for 90-130 seconds, which causes both the applied force and the piston displacement speed to decrease. When the piston displacement stabilizes, the applied force also stabilizes.
[0159] Since the inner diameter of the hollow cylinder of the experimental apparatus is 50 mm, the stress of the freshly mixed liquid mortar mixture when pressure is applied can be calculated using the following formula.
[0160] Since the height of the hydraulic cylinder of the experimental apparatus is 150 mm and the height of the piston is 20 mm, the initial height of the fresh liquid mortar mixture in the mold before the pressure is applied can be assumed to be 130 mm. The strain of the fresh liquid mortar mixture when the pressure is applied can be calculated using the formula (30) provided below.
[0161] Fig.26 Depicted are: (a) the stress-volume strain curve of the CDG mortar specimen; (b) the stress-volume strain curve of the mortar specimen. Specifically, Fig.26 The relationship between stress and volumetric strain of CDG mortar and mortar specimens with three mixing ratios is shown. The stress variation trend of CDG mortar and mortar follows a similar pattern as the variation of applied pressure over time. The stress value first increases almost linearly and then reaches a peak value of 10–11 MPa. Then the stress value decreases and finally stabilizes at 4.5–5.5 MPa, while the strain stops in the interval of 0.11–0.15.
[0162] Since the fresh mortar in the hydraulic cylinder is in a liquid or semi-liquid state, the Pascal principle applies, so that the piston can transfer pressure to the fresh mortar. Therefore, the fresh mortar in the hollow cylinder is first subjected to a pressure of 10-11 MPa, and then to a stable pressure of 4.5-5.5 MPa, which can last for a specific time (24 hours / 8 hours).
[0163] [Technical Solution (II) - Part 1.4: Sample Preparation]: Fig. 27Pictures of six mortar and CDG mortar samples with three typical mix ratios are depicted. With reference to some standards, the mixtures can be designed at the following six weight ratios (water: cement: aggregate) of 0.4:1:1.25, 0.4:1:1, 0.5:1:1.25, 0.5:1:1, 0.7:1:1.25 and 0.7:1:1 respectively; which are used for each of the two aggregate types, CDG and sand, for comparative experimental studies. For CDG and mortar specimens with mix ratios of 0.5:1:1.25 and 0.5:1:1, 8 hours of pressurization will be applied to compare the effects of pressurization of different durations.
[0164] Therefore, a number of different test pieces were manufactured and tested, as shown in Table 12, and Fig.28 Pictures of six mortars with three typical mix ratios and six CDG mortars are shown. Table 12: Mixture design and density and axial compressive strength results for multiple CDG or mortar specimens
[0165] [Technical Solution (II) - Part 2: Results and Discussion]: Fig.29 The density value variation relationship diagram of multiple mortar specimens made of CDG and Xiamen standard sand under the conditions of initial pressure of 10MPa or 0MPa and different water contents is shown; Fig.30 The graph shows the change relationship of uniaxial compressive strength of multiple mortar specimens made of CDG and Xiamen standard sand under initial pressure of 10MPa or 0MPa and different water contents.
[0166] Comprehensive Table 12 and Fig.29 and Fig.30 , which shows the density and compressive strength (axial compressive strength) values of multiple mortar specimens made with six mixing ratios, with or without the initial application of 10 MPa compressive pressure for 24 or 8 hours.
[0167] [Technical Solution (II) - Section 2.1: Density Results]: This section discusses the effects of water-cement-aggregate ratio, the effect of initial pressurization, the comparison between CDG and sand, and the key findings.
[0168] [Technical Solution (II) - Section 2.1.1: Effect of Water-Cement-Aggregate Ratio]: In general, the density values of mortar specimens with a water:cement:aggregate ratio of x:1:1.25 were higher than those of specimens with a water:cement:aggregate ratio of x:1:1, where x = 0.4, 0.5, and 0.7, indicating that the more aggregates, the higher the density. In addition, as x increased from 0.4 to 0.5 to 0.7 (e.g., the water content (ratio of water mass to solid mass) increased from 17.78% to 35.00%), the density values initially decreased, then increased, and then decreased. For example, four CDG specimens (x:1:1.25) initially pressurized at 10 MPa had density values of 2075, 2167, 2193, and 1958 kg / m3 (average value = 2099 kg / m3) at x = 0.4, 0.5, and 0.7, respectively. The other four CDG specimens (x:1:1) with an initial pressurization of 10 MPa had density values of 1931, 2061, 2115 and 1747 kg / m3 (average value = 1964 kg / m3) at x = 0.4, 0.5 and 0.7, respectively.
[0169] [Technical Solution (II) - Section 2.1.2: Effect of Initial Pressurization]: Initial pressurization of 10 MPa can significantly increase the density values of specimens of all six mixed design types. For example, the average density value of four CDG specimens (x: 1: 1.25) with an initial pressurization of 10 MPa is 2099 kg / m3. The average density value of four CDG specimens (x: 1: 1.25) with an initial pressurization of 0 MPa is 1975 kg / m3. The average increase is 6.3%, which is a high increase. In addition, the effect of initial pressurization for a duration of 8 hours on the increase in density is similar to that of initial pressurization for a duration of 24 hours.
[0170] [Technical Solution (II) - Section 2.1.3: Comparison of CDG and Sand]: In general, the density values of mortar specimens made with CDG are smaller than those made with sand. However, the density (2167 kg / m3) of the CDG-cement mortar specimen (0.5:1:1.25) with 24 hours and initial pressurization of 10 MPa is slightly greater than the density (2132 kg / m3) of the mortar specimen under the same conditions. While the density (2115 kg / m3) of the CDG mortar specimen (0.5:1:1) with 8 hours and initial pressurization of 10 MPa is slightly less than the density (2162 kg / m3) of the mortar specimen under the same conditions. These results indicate that initial pressurization can produce CDG-cement mortar with similar / higher density values compared to ordinary mortar using sand as aggregate.
[0171] [Technical Solution (II) - Section 2.1.4: Main Findings]: More aggregate content can increase the density of mortar specimens, while more water content can reduce the density. The optimal water content is about 22.22% to 25.00% (water-cement ratio = 0.5:1). 10MPa initial pressurization can significantly increase the density values of all specimens with different mix designs and fine aggregates. Initial pressurization can make CDG mortar specimens have similar density values as mortar specimens.
[0172] [Technical Solution (II) - Section 2.2: Results of Axial Compressive Strength]: The following content provides the effect of water-cement-aggregate ratio, the effect of initial pressurization, the comparison of CDG and sand, and the key factors affecting these.
[0173] [Technical Solution (II) - Section 2.2.1: Effect of Water-Cement-Aggregate Ratio]: Generally, mortar specimens with a water:aggregate:cement ratio of x:1:1.25 have axial compressive strength values similar to those with a water:aggregate:cement ratio of x:1:1, where x can be equal to 0.4, 0.5, and 0.7, respectively. However, as the water content increases, the axial compressive strength values of the mortar specimens increase significantly and then drop sharply. For example, the axial compressive strength values of the four CDG specimens (x:1:1.25) with an initial pressure of 10 MPa are 27.6, 44.3, 41.0, and 14.1 MPa (average value = 31.75 MPa), where x is equal to 0.4, 0.5, and 0.7, respectively. The axial compressive strength values of the other four CDG specimens with an initial pressure of 10 MPa were 29.0, 30.4, 44.4, and 13.5 MPa (average value = 29.33 MPa), where x was equal to 0.4, 0.5, and 0.7, respectively.
[0174] [Technical Solution (II) - Section 2.2.2: Effect of Initial Pressurization]: For all six mix design types, an initial pressurization of 10 MPa can significantly increase the axial compressive strength of the specimens. For example, the average axial compressive strength of the four CDG specimens (x:1:1.25) after an initial pressurization of 10 MPa was 31.75 MPa, while the average axial compressive strength of the four CDG specimens (x:1:1) without initial pressurization was 16.20 MPa, with an average increase of 95.99%, which is significantly higher. The results show that the effects of initial pressurization for 8 hours and 24 hours on the axial compressive strength of the specimens are similar.
[0175] [Technical Solution (II) - Section 2.2.3: Comparison of CDG and Sand]: Overall, the axial compressive strength values of CDG mortar specimens were lower than those of mortar specimens with an initial pressurization of 0 MPa. The axial compressive strength value of CDG-cement mortar (0.5:1:1.25) at 24 hours and 10 MPa initial pressurization (44.3 MPa) was similar to the axial compressive strength value of mortar specimens under the same conditions (44.9 MPa). These results indicate that initial pressurization can produce CDG mortar specimens with similar or higher axial compressive strength values than mortar specimens.
[0176] [Technical Solution (II) - Section 2.2.4: Main Findings]: Water content significantly affects the axial compressive strength of mortar specimens. The optimum water content is about 22.22% to 25.00% (water-cement ratio = 0.5:1). Under 0MPa pressure, the axial compressive strength value of CDG-cement mortar specimens is significantly smaller than that of mortar specimens. 10MPa initial pressure can significantly increase the axial compressive strength value of mortar specimens and produce CDG mortar specimens with similar high axial compressive strength value (44.3MPa) as mortar specimens.
[0177] [Technical Solution (II) - Part 2.3: X-ray Fractional Observation]: Fig.31 The CT images and data analysis of representative specimens are depicted, where: Part (a), Part (b), Part (c), and Part (d) are cross-sectional CT images of pressurized and zero-pressurized CDG and concrete specimens; Part (e) is the cumulative density gradation curve. In this stage, micro-CT scanner TOSCANER-3000 was used to conduct microstructural tests on CDG and mortar specimens with a water: cement: aggregate ratio of 0.7:1:1.25, and the specimens were cut into slices with a width of 10 mm. Fig.31 The four CT images in parts (a), (b), (c), and (d) represent two mortar specimens and two CDG specimens with initial pressurization of 10 MPa and 0 MPa, respectively. The grayscale of each pixel in the CT image can represent the relative density of the pixel area of the CDG or mortar specimen. Each grayscale is an integer between 0 and 255, which occupies the same pixel area in the cross section of the specimen. The darker the grayscale of the pixel, the lower the density of the pixel. The grayscale of the void pixel is 0. Therefore, the grayscale of all pixels can be used to obtain the density distribution of the specimen slice. The following formula is used to calculate the density level of a pixel based on its grayscale level.
[0178] Among them, n j is the total number of pixels of the jth gray level, j = 0 to 255. Fig.31The measured density values of the four CT images in parts (a), (b), (c), and (d) are 2193, 2056, 1958, and 1898 kg / m3, respectively.
[0179] Accordingly, the cumulative density gradient curve can be calculated using the following formula.
[0180] for Fig.31 The cumulative density gradient curves of the four CT images in parts (a), (b), (c), and (d) are as follows: Fig.31 For each CT image, the percentage of void (0 grayscale) pixels to the total number of pixels can be used to represent the void ratio of the specimen, which can be calculated using formula (5) at the 0th density. Fig.31 The four CT images in part (a), part (b), part (c), and part (d) have void ratios of 1.354%, 5.036%, 1.174%, and 8.718%, respectively. The void ratios of the CDG and mortar specimens with an initial pressure of 10 MPa are 1.174% and 1.354%, respectively. The porosity of the CDG and mortar specimens with an initial pressure of zero is 8.718% and 5.036%, respectively, 13.47%, and 26.89%, respectively. Therefore, the initial pressure of 10 MPa can significantly reduce the porosity.
[0181] Secondly, by Fig.31 From part (e), we can see that the cumulative area percentages of CDG and mortar specimens with relative density below 1.5 kg / m3 with initial pressure of 10 MPa are 3.540% and 4.948%, respectively, which are significantly lower than 10.975% and 17.715% of CDG and mortar specimens with initial pressure of zero. When the initial pressure is zero, the porosity of CDG mortar specimen is 8.718%, which is higher than the porosity of mortar specimen 5.036%. When the initial pressure is 10 MPa, the porosity of CDG mortar specimen is 1.174%, which is slightly lower than the 1.354% of mortar specimen. The results show that initial pressure can prepare CDG mortar with the same low porosity as mortar specimen.
[0182] In general, when the initial pressure was 10 MPa, the bonding areas of the two cumulative density gradation curves of the CDG and mortar specimens were much narrower than those of the two curves of the two specimens when the initial pressure was zero, indicating that densification was achieved as a whole when the initial pressure was 10 MPa.
[0183] [Technical Solution (II) - Part 3: Conclusion of Technical Solution (II)]: The results of Technical Solution (II) show that the axial compressive strength and density of the non-pressurized CDG mortar specimens are less than those of the non-pressurized mortar specimens. And the porosity of the non-pressurized CDG mortar specimens is greater than that of the non-pressurized mortar specimens. This is because the large amount of clay particles in CDG will absorb a large amount of water due to their small particle size and large specific surface area, thereby reducing the hydration efficiency of cement. On the other hand, initial pressurization of the liquid mixture can significantly increase the density and axial compressive strength values of CDG and mortar specimens with different mixing ratios. In addition, pressurization can reduce their porosity and improve uniformity in compaction. Therefore, it is demonstrated that the initial pressurization method has the potential to produce mortars and concretes with high compressive strength and low porosity in actual engineering. In this case, CDG soil also has the potential to be used as fine aggregate in the production of initial pressurized mortars and concrete.
[0184] In technical solution (two), a new type of high-quality mortar material was prepared by using the device for applying initial pressure to fresh liquid mortar proposed in the present invention. The results show that initial pressurization of the liquid mixture significantly enhances the properties of CDG and mortar specimens with different mixing ratios. Table 2 shows a summary of these enhanced properties of mortar specimens with initial pressurization of 10MPa. Specifically, the density value can be increased by up to 8.31%, and the axial compressive strength value can be increased by up to 187.43%. In addition, pressurization reduces the porosity and improves the uniformity in compaction. Therefore, it is proved that in actual engineering, initial pressurization can be used to produce mortar and concrete with high compressive strength and low porosity. Table 13: Summary of reinforcement properties of mortar specimens with initial pressure of 10 MPa
[0185] In the present disclosure, the “ratio”, “proportion”, “mixing ratio” and “mixing ratio” mentioned include similar or identical terms such as weight ratio and mass ratio.
[0186] Although several embodiments of the present invention have been described, it will be appreciated by those skilled in the art that changes may be made to the present embodiments without departing from the principles and spirit of the present invention, the scope of which is defined in the claims and their equivalents. The above description of the present invention is for illustration and description purposes only. It is not intended to be exhaustive or to limit the invention to the precise form disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments described are intended to best explain the principles and practical applications of the present invention so that other skilled in the art can understand the various embodiments and modifications suitable for a particular purpose.
Claims
1. A method for actively applying initial steady-state pressure to fresh liquid or semi-liquid concrete, characterized in that: include: adding materials including aggregate, cement and water into a container to form a liquid mixture; stirring the mixture to obtain a fresh liquid or semi-liquid concrete mixture; pouring the fresh liquid or semi-liquid mixture into a mold or template, and smoothing the surface of the fresh liquid or semi-liquid mixture after the mold is filled; Mounting a top plate with one or more hollow cylinders on the mold or formwork to cover the fresh liquid or semi-liquid mixture, thereby sealing the mold or formwork, wherein the inner diameter of the hollow cylinder is 10 mm to 1000 mm; Pouring additional fresh liquid or semi-liquid mixture into the hollow cylinder and smoothing the surface of the additional mixture on the top; Placing a cylindrical piston on the surface of the fresh liquid or semi-liquid mixture in the hollow cylinder; Pressurizing the piston to apply steady-state pressure to the fresh liquid or semi-liquid mixture in the completely sealed mold or template, so that the fresh liquid or semi-liquid mixture in the hollow cylinder becomes part of the fresh mixture in the mold or template; After a period of time when the steady-state pressure is applied, the piston pressure is unloaded; When the mixture hardens to a sufficient strength, the mold or formwork is removed to obtain a concrete component.
2. The method according to claim 1, characterized in that After the pressure is applied to the fresh liquid or semi-liquid mixture, the pressure is maintained at a steady state for a specified period of time, and after the specified period of time, the pressure is unloaded.
3. The method according to claim 1, characterized in that The initial pressure is in the range of 1 MPa to 50 MPa.
4. The method according to claim 1, characterized in that: The use of the mold or formwork is determined according to the size of the concrete component.
5. The method according to claim 1, characterized in that After applying the initial pressure and before the step of unloading the pressure, the method further includes: maintaining the applied pressure at a steady state for a given time.
6. A pressurized system for carrying out the method according to claim 1, characterized in that: include: The mold or form part, which appears cylindrical or cubic; A loading portion, disposed above the mold or template portion; as well as A hollow cylinder and a cylindrical piston and a hydraulic jack or hydraulic cylinder are used to drive the loading part, wherein the hydraulic jack or hydraulic cylinder is connected to the cylindrical piston so as to cooperate to pressurize the mold or template part to apply an active initial steady-state pressure to the fresh liquid mixture in the mold or template.
7. A method for pouring fresh liquid or semi-liquid mortar or concrete by applying active initial pressure, characterized in that: include: mixing materials including water, cement, and aggregate in a container to form a mixture; Stirring the mixture with a stirrer to form a fresh liquid or semi-liquid mixture; Place the bottom piston into the hollow cylindrical mold; placing the fresh liquid or semi-liquid mixture into the hollow cylindrical mold; placing the top piston into the hollow cylindrical mold; positioning the hollow cylindrical mold on a bottom load sensor; Using a hydraulic jack to apply pressure to the top piston, thereby applying pressure to the fresh liquid or semi-liquid mixture to compress it; After a period of time when steady-state pressure is applied, the top piston pressure is unloaded; The hardened mortar or concrete in the mold is demoulded by the upward movement of the bottom piston.
8. The method according to claim 7, characterized in that After the pressure is applied to the fresh liquid or semi-liquid mixture, the pressure is maintained at a steady state for a specified period of time, and after the specified period of time, the pressure is unloaded.
9. The method according to claim 7, characterized in that: During the process of applying the pressure to the fresh liquid or semi-liquid mixture, the method also includes: moving the top piston downward or moving the bottom piston upward, wherein when the top piston moves downward, the bottom remains stationary, and when the bottom piston moves upward, the top piston remains stationary, and the fresh liquid or semi-liquid mixture in the cylindrical mold is compressed.